Globalisation, economic policy, and equity: the case of Malaysia - Yusoff, Mohammed; Abu Hasan, Fauziah; Abdul Jalil, Suhaila (OECD, 2000)
The post independence social and economic development of Malaysia has been guided by a series of five-year development plans which have successfully implemented and transformed the economy from an agricultural based to the modern technological manufacturing based economy. The achievement was most evident during the period of the New Economic Policy as clearly indicated by the significant reduction in the absolute poverty level and more participation of the Bumiputra in the modern business sector. In Malaysia, the aspects of economic growth and equity have always been emphasized in her development plans to ensure a just and equitable distribution of national wealth in the economy. The development strategies focused on the diversification of industrial structure, enhancing human resource development, promote the use of modern technology to sustain growth momentum and balanced socio-economic development. The roles of the government in the economy have been gradually reduced through privatization and the private sector has to play a bigger role in creating economic activities through expanding private investment. The relatively successful reductions in inequality and poverty can be attributed to the growth of the industrial sector. Foreign investments were encouraged through liberalization of the procedures and rules and maintain liberal policy on foreign equity participation in the manufacturing and tourism sectors. In order to improve the international competitiveness, Malaysia had changed her industrial structure moving away from labor intensive industries into a more high technology industries to reduce its unit cost of production. And finally Malaysia has already made progress to develop her financial and capital markets for efficient mobilization of saving to meet the needs of the private sector long-term investment fund.